2014
DOI: 10.1111/ijfs.12633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gums on viability and βgalactosidase activity of Lactobacillus spp. in milk drink during refrigerated storage

Abstract: Summary The viability and β‐galactosidase activity of four Lactobacillus strains in milk drink containing gums during 28 days of refrigerated storage at 4 °C were assessed. The population of Lactobacillus rhamnosus GGB101 and Lactobacillus rhamnosus GGB103 were maintained, whereas the population of Lactobacillus reuteri DSM20016 and Lactobacillus reuteri SD2112 significantly decreased. The recommended level of 6 log CFU g−1 was exceeded for all tested trains throughout storage. The highest viable number of Lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Ziaolhagh and Jalali, (), reported that xanthan gum could stimulate the growth of Bifidibacterium lactis in Doogh samples. It has been reported that the population of Lactobacillus rhamnosus as a probiotic in the food product containing carrageenan–maltodextrin was higher compared to the control sample (Karlton‐Senaye, Tahergorabi, Giddings, & Ibrahim, ). These results thus indicate that this CSG could maintain the viability of probiotic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Ziaolhagh and Jalali, (), reported that xanthan gum could stimulate the growth of Bifidibacterium lactis in Doogh samples. It has been reported that the population of Lactobacillus rhamnosus as a probiotic in the food product containing carrageenan–maltodextrin was higher compared to the control sample (Karlton‐Senaye, Tahergorabi, Giddings, & Ibrahim, ). These results thus indicate that this CSG could maintain the viability of probiotic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Food products comprised of probiotic bacteria have therapeutic benefits such as response improvement of the immune system, reduction in cholesterol, reduction in lactose intolerance, faster treatment of diarrhoea and lower risk of colon cancers (Karlton‐Senaye et al , ). In order to avail beneficial therapeutic effects, the lowest level of probiotic live microbes at the time of consumption has been recommended to be 10 6 –10 7 cfu mL −1 (Silva et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic dairy products are one of the most important groups of functional foods containing enough count of live microorganisms and influencing host health (Batista et al, 2015;Dantas et al, 2016;Felicio et al, 2016;Pereira et al, 2016a,b). Products comprised of probiotic bacteria have therapeutic benefits such as response improvement of the immune system, reduction in cholesterol, reduction in lactose intolerance, faster treatment of diarrhoea and lower risk of colon cancers (Karlton-Senaye et al, 2015). In order to have a beneficial effect of probiotics on the gut, the recommended count of viable cells should be 10 8 -10 10 CFU per day, which corresponds to 10 6 -10 8 CFU g À1 in the product at the time of consumption (Albadran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…bulgaricus (Batista et al, 2015;Perina et al, 2015). The production of probiotic yoghurt has faced specific problems, because probiotic bacteria are subjected to unsuitable conditions such as pH decrease and increment in concentration of organic acids during cold storage; therefore, probiotic strains could not completely sustain their vitality in the final yoghurt product or may even alter taste of yoghurt (Karlton-Senaye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%